GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Exposure to municipal solid waste incinerators and cancer risk in surrounding populations: A systematic review and meta-analysis - Carolina Capitão; Osvaldo Santos; Raquel Martins; Mónica Fialho; Rodrigo Feteira-Santos; Ricardo R. Santos; Murilo Engel; Anthony Purece; Jurgen Buekers; Tommaso Filippini; Ana Virgolino (Environmental Toxicology and Pharmacology, 2026)

Data Considerations for Estimating Ambient Heat Exposure for Environmental Epidemiological Studies - Emma L. Gause; Talia Feldscher; Zachary Popp; Keith R. Spangler; Sean C. Mueller; Quinn H. Adams; TC Chakraborty; Lucy R. Hutyra; Allison James; Thomas J. Luben; Dany Doiron; Carina J. Gronlund; et al. (Current Environmental Health Reports, 2026)

Decoding sebaceous gland functions and diseases: insights from domestic animals - Helga Pfannkuche; Juliane Maus; Kathrin M. Engel; Jürgen Schiller; Marlon R. Schneider (Veterinary Research Communications, 2026)
Skin sebaceous glands (SGs) synthesize and secrete sebum, a mixture of lipids and cellular debris that defends the external body surface against physicochemical challenges. Recent data define the SG as a dynamic entity with potential functions beyond skin protection, including immunomodulatory actions and the regulation of energy metabolism. We postulate that the SG also has important, unrecognized roles in physiological and pathological processes in domestic animals. Conversely, data derived from domestic animals may have translational relevance for humans. This review article summarizes SG structural and functional features in the most widespread species domesticated for food (cattle, sheep, goats, and pigs), work (horses), and companionship (dogs and cats). Our survey reveals hitherto unrecognized roles of the SG in diverse pathophysiological processes. Among other fascinating facts, we learn that sebum has an exquisite and unique lipid composition in each of the considered species. Furthermore, sebum is essential for e.g., wool production but also a carrier for the most important cat protein causing allergic reactions in humans, and dogs and cats may develop a SG-related skin illness resembling acne that is potentially relevant as a model for the human disease. This critical review provides a foundation for future interdisciplinary studies in a largely neglected area with great potential for advancing animal welfare and human health.

Decreased Length of Locus Coeruleus Norepinephrine Axons and Increased Amyloid Beta Pathology in Male APP/PS1 Mice During Protracted Abstinence From Alcohol - Ivy J. Z. Garland; Shaydel Engel; Matthew Scalf; Nichole R. Payne; Anna M. Lee; Steven M. Graves (Neurotoxicity Research, 2026)
Alzheimer’s disease (AD) is the leading cause of dementia and evidence suggests that alcohol, the most commonly used addictive substance, may increase AD risk. Locus coeruleus (LC) neurons are the primary source of norepinephrine in the brain and these neurons degenerate early in AD. In rodent models, lesioning the LC increases amyloid beta (Aβ) pathology suggesting that LC integrity and norepinephrine signaling obstruct Aβ pathogenesis. We recently reported a decrease in the number of LC norepinephrine neurons and increased Aβ pathology when measured after protracted abstinence from chronic intermittent alcohol consumption in female APP/PS1 mice. Clinically, female subjects are at a higher risk for AD; additionally, female mice consume more alcohol than male mice making it unclear as to whether alcohol consumption would produce similar adverse outcomes in male subjects. To address this gap, male APP/PS1 and non-transgenic mice underwent chronic intermittent access (IA) to alcohol followed by protracted abstinence with water drinking controls run in parallel, consistent with our prior study. In contrast to our previous results with female mice, the number of LC norepinephrine neurons was unchanged in male APP/PS1 mice that had IA to alcohol; however, the length of LC axons was decreased and Aβ pathology was increased in male APP/PS1 mice that consumed alcohol. These data demonstrate that alcohol consumption during early adulthood results in negative consequences in male APP/PS1 mice, although the effect may not be as severe as previously observed in female mice.

The impact of feeding styles on unhealthy dietary intakes and weight-for-length z-scores: Investigating sweet beverages and snack food consumption during early childhood in a diverse sample - Catherine A. Serwatka; Lauren M. Smith; Amy M. Moore; Tarunjot Sethi; Hideko Engel; Amy R. Smith; Kai Ling Kong (Appetite, 2026)

Associations between airborne crude oil chemicals and neurological symptoms among workers in the gulf long-term follow-up study - Kristen N. Cowan; Emily J. Werder; Kaitlyn G. Lawrence; Richard K. Kwok; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Tran B. Huynh; Sudipto Banerjee; Gurumurthy Ramachandran; W. Braxton Jackson; Frankie LaPorte; et al. (Science of The Total Environment, 2025)

Association of oil spill cleanup-related hydrocarbon exposure with hypertension and blood pressure in the Gulf Long-term Follow-up Study - Opal P. Patel; Jessie K. Edwards; Anna M. Kucharska-Newton; Eric A. Whitsel; W. Braxton Jackson; Kaitlyn G. Lawrence; Patricia A. Stewart; Mark R. Stenzel; Lawrence S. Engel; Dale P. Sandler (Science of The Total Environment, 2025)

Reconsidering palliative radiotherapy in addition to PD-1 blockade for non-small cell lung cancer: results from the FORCE phase II trial (AIO/YMO-TRK-0415) - Farastuk Bozorgmehr; Inn Chung; Jürgen R. Fischer; Marc Bischof; Akin Atmaca; Sophie Wetzel; Martin Faehling; Dirk Bottke; Martin Wermke; Esther G. C. Troost; Cornelia Kropf-Sanchen; Thomas Wiegel; et al. (Clinical & Experimental Metastasis, 2025)
Introduction of immune checkpoint inhibitors (ICI) has improved overall survival (OS) for advanced non-small cell lung cancer (NSCLC). However, responses differ greatly amongst patients. Additional radiotherapy (RT) may promote tumor-specific immunity and synergize with ICI to improve tumor control. The multicenter phase II FORCE trial evaluated safety and efficacy of nivolumab with additional palliative radiotherapy (5 × 4 Gy) as clinically indicated in pre-treated metastatic non-squamous NSCLC (group A, n = 41), including pretreated patients without an indication for radiotherapy in a parallel cohort as real-world controls (group B, n = 60). With an objective response rate (ORR) of 8.3% in group A ( n = 41), the primary endpoint was not met ( p = 0.991). ORR in group B ( n = 60) was 23.8%. Patient characteristics indicated a significantly poorer baseline clinical condition for group A compared to B, including worse Eastern Cooperative Oncology Group (ECOG) performance status (PS, p = 0.020) and more metastatic sites ( p = 0.009). Consequently, group A had shorter progression-free survival (median PFS, 1.9 versus 3.7 months, hazard ratio [HR] 1.69 [95% CI (1.10, 2.58)]) and OS (median 6.0 versus 12.6 months, HR 1.75 [95% CI (1.07, 2.84)]). In multivariable analyses for the intention-to-treat (ITT) population, ORR, PFS and OS were inversely associated with the patients’ ECOG PS (ORR odds ratio [OR] 0.126, p = 0.004) and correlated positively with tumor PD-L1 expression (ORR OR 12.8, p = 0.022), but not with radiotherapy administration ( p = 0.169–0.854). Adverse events were distributed equally in both groups. Addition of palliative radiotherapy to nivolumab was safe and feasible, but not associated with improved efficacy. Patients with an indication for palliative radiotherapy have an inherently worse prognosis which cannot be overcome by radiation-induced immunostimulation. Clinical features and PD-L1 expression influence clinical outcomes more than radiotherapy administration and should be considered when evaluating the effectiveness of immuno-/radiotherapy combinations. ClinicalTrials.gov identifier : NCT03044626

Oil spill cleanup related exposures to benzene, toluene, ethylbenzene, xylenes, and n-hexane and incident diabetes mellitus - Hanna V. Jardel; Alexander P. Keil; Chantel L. Martin; David B. Richardson; Mark R. Stenzel; Patricia A. Stewart; Kate E. Christenbury; Lawrence S. Engel; Dale P. Sandler (Environmental Research, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Organic Geochemistry and Paleodepositional environment of the Mushorah Formation in Sufaya and Ain Zala oilfields, Northwestern Iraq - Mohamed W. Alkhafaji; Mohamed R. M. Ahmed; Taher Mahmood Taha; Anwaar S. Al-Maadhidi; Jacques Connan; Michael H. Engel (Carbonates and Evaporites, 2025)

Prevalence of cardiovascular disease risk factors associated with residential natural hazard risk - Kaitlyn G. Lawrence; Marina R. Sweeney; Emily J. Werder; Casey Zuzak; Melanie Gall; Christopher T. Emrich; Ian D. Buller; W. Braxton Jackson; Dazhe Chen; Kate E. Christenbury; Lawrence S. Engel; Dale P. Sandler (Science of The Total Environment, 2025)

RIce-Net: Integrating ground-based cameras and machine learning for automated river ice detection - Mahmoud Ayyad; Marouane Temimi; Mohamed Abdelkader; Moheb M.R. Henein; Frank L. Engel; R. Russell Lotspeich; Jack R. Eggleston (Environmental Modelling & Software, 2025)

Stingless bee honey: Nutraceutical properties and urgent call for proposed global standards - Patricia Vit; Bajaree Chuttong; Elia Ramírez-Arriaga; Eunice Enríquez; Zhengwei Wang; Cleofas Cervancia; Favio Vossler; Sammy Kimoloi; Michael S. Engel; Ricardo R. Contreras; Christopher A. Mduda; Francisco Tomás-Barberán (Trends in Food Science & Technology, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Melt processing of chemically modified cellulosic fibres with only water as plasticiser: Effects of moisture content and processing temperature - Emile R. Engel; Giada Lo Re; Per A. Larsson (Carbohydrate Polymers, 2025)

Estimating rates of change to interpret quantitative wastewater surveillance of disease trends - David A. Holcomb; Ariel Christensen; Kelly Hoffman; Allison Lee; A. Denene Blackwood; Thomas Clerkin; Javier Gallard-Góngora; Angela Harris; Nadine Kotlarz; Helena Mitasova; Stacie Reckling; Francis L. de los Reyes; et al. (Science of The Total Environment, 2024)

Sediment export from an Alpine proglacial area under a changing climate: Budgets, rates, and geomorphological processes - Sara Savi; Felix Pitscheider; Michael Engel; Velio Coviello; Manfred R. Strecker; Francesco Comiti (Geomorphology, 2024)

Perspectives on Conservation Impacts of the Global Primate Trade - Gal Badihi; Daniel R. K. Nielsen; Paul A. Garber; Mike Gill; Lisa Jones-Engel; Angela M. Maldonado; Kerry M. Dore; Jennifer D. Cramer; Susan Lappan; Francine Dolins; Emerson Y. Sy; Agustin Fuentes; et al. (International Journal of Primatology, 2024)
The global trade in nonhuman primates represents a substantial threat to ecosystem health, human health, and primate conservation worldwide. Most of the primate trade involves trade for pet-keeping, consumption, or biomedical experimentation. We present an overview of international primate trade through five case studies; each describes a different facet of this trade. We draw on published scientific literature, media outlets, and open access datasets, including the CITES Trade Database to build these case studies. Case study 1 describes the role of introduced island populations of Macaca and Chlorocebus in trade for biomedical experimentation; case study 2 covers the global health threats posed by the primate trade, including zoonotic disease transmission once animals enter the trade pipeline; case study 3 addresses the ways that changing patterns of primate trade, from local markets to online, have increased the demand for primates as pets; case study 4 recognizes the role that local environmental activism can play in mitigating trade; and case study 5 shows variation between global regions in their contribution to the primate trade. We recommend greater oversight of primate trade, especially domestic trade within primate range countries, and real-time reporting to CITES to accurately track primate trade. Effective conservation-focused regulations that can minimise the negative effects of primate trade must be tailored to specific regions and species and require transparency, careful regulation, field research, and an understanding of the magnitude of this trade.

Associations of a toenail metal mixture with attention and memory in the Gulf long-term follow-up (GuLF) study - Joyce J.Y. Lin; Jordan R. Kuiper; Aisha S. Dickerson; Jessie P. Buckley; Heather E. Volk; Diane S. Rohlman; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Lawrence S. Engel; Ana M. Rule (Science of The Total Environment, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Biodiversity responses to Lateglacial climate change in the subdecadally-resolved record of Lake Hämelsee (Germany) - S. Engels; C.S. Lane; W.Z. Hoek; I. Baneschi; A. Bouwman; E. Brogan; C. Bronk Ramsey; J. Collins; R. de Bruijn; A. Haliuc; O. Heiri; K. Hubay; et al. (Quaternary Science Reviews, 2024)

Isotopic and chemical signatures of high mountain rivers in catchments with contrasting glacier and rock glacier cover - S. Brighenti; M. Engel; R. Dinale; W. Tirler; G. Voto; F. Comiti (Journal of Hydrology, 2023)

Exposure to volatile hydrocarbons and neurologic function among oil spill workers up to 6 years after the Deepwater Horizon disaster - Dazhe Chen; Emily J. Werder; Patricia A. Stewart; Mark R. Stenzel; Fredric E. Gerr; Kaitlyn G. Lawrence; Caroline P. Groth; Tran B. Huynh; Gurumurthy Ramachandran; Sudipto Banerjee; W. Braxton Jackson II; Kate Christenbury; et al. (Environmental Research, 2023)

The effect of mobility-related anxiety on walking across the lifespan: a virtual reality simulation study - Tiphanie E. Raffegeau; Mindie Clark; Bradley Fawver; Benjamin T. Engel; William R. Young; A. Mark Williams; Keith R. Lohse; Peter C. Fino (Experimental Brain Research, 2023)

Structure and composition of natural ferrihydrite nano-colloids in anoxic groundwater - Maya Engel; Vincent Noël; Samuel Pierce; Libor Kovarik; Ravi K. Kukkadapu; Juan S. Lezama Pacheco; Odeta Qafoku; J. Ray Runyon; Jon Chorover; Weijiang Zhou; John Cliff; Kristin Boye; et al. (Water Research, 2023)

Gestational organophosphate ester exposure and preschool attention-deficit/hyperactivity disorder in the Norwegian Mother, Father, and Child cohort study - Amber M. Hall; Amanda M. Ramos; Samantha SM. Drover; Giehae Choi; Alexander P. Keil; David B. Richardson; Chantel L. Martin; Andrew F. Olshan; Gro D. Villanger; Ted Reichborn-Kjennerud; Pål Zeiner; Kristin R. Øvergaard; et al. (International Journal of Hygiene and Environmental Health, 2023)

Detection of SARS-CoV-2 RNA in wastewater and comparison to COVID-19 cases in two sewersheds, North Carolina, USA - Alyssa M. Grube; Collin K. Coleman; Connor D. LaMontagne; Megan E. Miller; Nikhil P. Kothegal; David A. Holcomb; A. Denene Blackwood; Thomas J. Clerkin; Marc L. Serre; Lawrence S. Engel; Virginia T. Guidry; Rachel T. Noble; et al. (Science of The Total Environment, 2023)

Melt processable cellulose fibres engineered for replacing oil-based thermoplastics - Giada Lo Re; Emile R. Engel; Linnea Björn; Manuel Guizar Sicairos; Marianne Liebi; Jan Wahlberg; Katarina Jonasson; Per A. Larsson (Chemical Engineering Journal, 2023)

Fine particulate matter and incident coronary heart disease events up to 10 years of follow-up among Deepwater Horizon oil spill workers - Dazhe Chen; Dale P. Sandler; Alexander P. Keil; Gerardo Heiss; Eric A. Whitsel; Gregory C. Pratt; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Sudipto Banerjee; Tran B. Huynh; Jessie K. Edwards; et al. (Environmental Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Local biodiversity change reflects interactions among changing abundance, evenness, and richness - Shane A. Blowes; Gergana N. Daskalova; Maria Dornelas; Thore Engel; Nicholas J. Gotelli; Anne E. Magurran; Inês S. Martins; Brian McGill; Daniel J. McGlinn; Alban Sagouis; Hideyasu Shimadzu; Sarah R. Supp; et al. (Ecology, 2022)
Biodiversity metrics often integrate data on the presence and abundance of multiple species. Yet our understanding of covariation between changes to the numbers of individuals, the evenness of species relative abundances, and the total number of species remains limited. Using individual‐based rarefaction curves, we show how expected positive relationships among changes in abundance, evenness and richness arise, and how they can break down. We then examined interdependencies between changes in abundance, evenness and richness in more than 1100 assemblages sampled either through time or across space. As predicted, richness changes were greatest when abundance and evenness changed in the same direction, and countervailing changes in abundance and evenness acted to constrain the magnitude of changes in species richness. Site‐to‐site differences in abundance, evenness, and richness were often decoupled, and pairwise relationships between these components across assemblages were weak. In contrast, changes in species richness and relative abundance were strongly correlated for assemblages varying through time. Temporal changes in local biodiversity showed greater inertia and stronger relationships between the component changes when compared to site‐to‐site variation. Overall, local variation in assemblage diversity was rarely due to repeated passive samples from an approximately static species abundance distribution. Instead, changing species relative abundances often dominated local variation in diversity. Moreover, how changing relative abundances combined with changes to total abundance frequently determined the magnitude of richness changes. Embracing the interdependencies between changing abundance, evenness and richness can provide new information to better understand biodiversity change in the Anthropocene.

Age-Dependent Dispersal and Relatedness in Tiger Sharks (Galeocerdo cuvier) - Margaret A. McClain; Neil Hammerschlag; Austin J. Gallagher; J. Marcus Drymon; R. Dean Grubbs; Tristan L. Guttridge; Matthew J. Smukall; Bryan S. Frazier; Toby S. Daly-Engel (Frontiers in Marine Science, 2022)
Understanding dispersal in large marine fauna is necessary for conservation, but movement patterns often vary widely by sex and life stage. In sharks, genetic studies have shown evidence of widespread male-biased dispersal, though tagging and tracking studies on the same populations show both sexes using site fidelity, including philopatry, and moving similar distances. We used a suite of microsatellite loci and DNA samples from 362 previously-tagged tiger sharks (Galeocerdo cuvier) in the northwestern Atlantic, including a large number of residential juveniles, to evaluate reproductive dispersal in light of demographic and published tracking data. We found that lumping size classes together resulted in genetic panmixia across sites, but systematic removal of large individuals showed significant population-level differentiation and three separate population clusters among juveniles less than 260 cm total length. Tests for relatedness found that 8.9% of our sample set was composed of first-order related pairs (N = 16), including several full siblings from different litters, a sign of multi-cycle genetic monogamy which carries implications for effective population size. By mapping genetic assignments of juveniles, we identified a signature of fine-scale genetic structure suggesting broad biparental site fidelity to reproductive habitat in the northeast Gulf of Mexico, which is concordant with both genetic and tracking data. Taken together, these findings demonstrate how lumping individuals from different life stages in genetic studies may obscure fine-scale genetic structure, confounding future conservation efforts.

Maternal Nanomaterial Inhalation Exposure: Critical Gestational Period in the Uterine Microcirculation is Angiotensin II Dependent - Krista L. Garner; Elizabeth C. Bowdridge; Julie A. Griffith; Evan DeVallance; Madison G. Seman; Kevin J. Engels; Caroline P. Groth; William T. Goldsmith; Kim Wix; Thomas P. Batchelor; Timothy R. Nurkiewicz (Cardiovascular Toxicology, 2022)

Climate-Biogeochemistry Interactions in the Tropical Ocean: Data Collection and Legacy - Gerd Krahmann; Damian L. Arévalo-Martínez; Andrew W. Dale; Marcus Dengler; Anja Engel; Nicolaas Glock; Patricia Grasse; Johannes Hahn; Helena Hauss; Mark J. Hopwood; Rainer Kiko; Alexandra N. Loginova; et al. (Frontiers in Marine Science, 2021)
From 2008 to 2019, a comprehensive research project, ‘SFB 754, Climate – Biogeochemistry Interactions in the Tropical Ocean,’ was funded by the German Research Foundation to investigate the climate-biogeochemistry interactions in the tropical ocean with a particular emphasis on the processes determining the oxygen distribution. During three 4-year long funding phases, a consortium of more than 150 scientists conducted or participated in 34 major research cruises and collected a wealth of physical, biological, chemical, and meteorological data. A common data policy agreed upon at the initiation of the project provided the basis for the open publication of all data. Here we provide an inventory of this unique data set and briefly summarize the various data acquisition and processing methods used.

Genetic evidence supports a range extension for the Brazilian cownose ray Rhinoptera brasiliensis in the western North Atlantic - Helen K. Weber; Christian M. Jones; Matthew J. Ajemian; Michael P. McCallister; Brent L. Winner; Gregg R. Poulakis; Dana M. Bethea; Lisa D. Hollensead; Daniel Zapf; John D. Swenson; Jill M. Hendon; Toby S. Daly‐Engel; et al. (Journal of Fish Biology, 2021)
We report 24 new records of the Brazilian cownose ray Rhinoptera brasiliensis outside its accepted geographic range. Sequencing of a 442‐base pair portion of the mitochondrial NADH dehydrogenase subunit 2 gene for 282 Rhinoptera samples revealed eight records off the east coast of the USA and 16 from the eastern Gulf of Mexico. Both sexes of all life stages were documented in all seasons over multiple years in the Indian River and Lake Worth lagoons, Florida, indicating that their range extends further in the western North Atlantic than previously described.

Stand growth and structure of mixed-species and monospecific stands of Scots pine (Pinus sylvestris L.) and oak (Q. robur L., Quercus petraea (Matt.) Liebl.) analysed along a productivity gradient through Europe - H. Pretzsch; M. Steckel; M. Heym; P. Biber; C. Ammer; M. Ehbrecht; K. Bielak; F. Bravo; C. Ordóñez; C. Collet; F. Vast; L. Drössler; et al. (European Journal of Forest Research, 2020)
Past failures of monocultures, caused by wind-throw or insect damages, and ongoing climate change currently strongly stimulate research into mixed-species stands. So far, the focus has mainly been on combinations of species with obvious complementary functional traits. However, for any generalization, a broad overview of the mixing reactions of functionally different tree species in different mixing proportions, patterns and under different site conditions is needed, including assemblages of species with rather similar demands on resources such as light. Here, we studied the growth of Scots pine and oak in mixed versus monospecific stands on 36 triplets located along a productivity gradient across Europe, reaching from Sweden to Spain and from France to Georgia. The set-up represents a wide variation in precipitation (456–1250 mm year −1 ), mean annual temperature (6.7–11.5 °C) and drought index by de Martonne (21–63 mm °C −1 ). Stand inventories and increment cores of trees stemming from 40- to 132-year-old, fully stocked stands on 0.04–0.94-ha-sized plots provided insight into how species mixing modifies stand growth and structure compared with neighbouring monospecific stands. On average, the standing stem volume was 436 and 360 m 3 ha −1 in the monocultures of Scots pine and oak, respectively, and 418 m 3 ha −1 in the mixed stands. The corresponding periodical annual volume increment amounted to 10.5 and 9.1 m 3 ha −1 year −1 in the monocultures and 10.5 m 3 ha −1 year −1 in the mixed stands. Scots pine showed a 10% larger quadratic mean diameter ( p < 0.05), a 7% larger dominant diameter ( p < 0.01) and a 9% higher growth of basal area and volume in mixed stands compared with neighbouring monocultures. For Scots pine, the productivity advantages of growing in mixture increased with site index ( p < 0.01) and water supply ( p < 0.01), while for oak they decreased with site index ( p < 0.01). In total, the superior productivity of mixed stands compared to monocultures increased with water supply ( p < 0.10). Based on 7843 measured crowns, we found that in mixture both species, but especially oak, had significantly wider crowns ( p < 0.001) than in monocultures. On average, we found relatively small effects of species mixing on stand growth and structure. Scots pine benefiting on rich, and oak on poor sites, allows for a mixture that is productive and most likely climate resistant all along a wide ecological gradient. We discuss the potential of this mixture in view of climate change.

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Genomic changes underlying host specialization in the bee gut symbiont Lactobacillus Firm5 - Kirsten M. Ellegaard; Silvia Brochet; German Bonilla‐Rosso; Olivier Emery; Natasha Glover; Noushin Hadadi; Kamil S. Jaron; Jan R. van der Meer; Marc Robinson‐Rechavi; Vladimir Sentchilo; Florian Tagini; Philipp Engel (Molecular Ecology, 2019)
Bacteria that engage in long‐standing associations with particular hosts are expected to evolve host‐specific adaptations that limit their capacity to thrive in other environments. Consistent with this, many gut symbionts seem to have a limited host range, based on community profiling and phylogenomics. However, few studies have experimentally investigated host specialization of gut symbionts and the underlying mechanisms have largely remained elusive. Here, we studied host specialization of a dominant gut symbiont of social bees, Lactobacillus Firm5. We show that Firm5 strains isolated from honey bees and bumble bees separate into deep‐branching host‐specific phylogenetic lineages. Despite their divergent evolution, colonization experiments show that bumble bee strains are capable of colonizing the honey bee gut. However, they were less successful than honey bee strains, and competition with honey bee strains completely abolished their colonization. In contrast, honey bee strains of divergent phylogenetic lineages were able to coexist within individual bees. This suggests that both host selection and interbacterial competition play important roles in host specialization. Using comparative genomics of 27 Firm5 isolates, we found that the genomes of honey bee strains harbour more carbohydrate‐related functions than bumble bee strains, possibly providing a competitive advantage in the honey bee gut. Remarkably, most of the genes encoding carbohydrate‐related functions were not conserved among the honey bee strains, which suggests that honey bees can support a metabolically more diverse community of Firm5 strains than bumble bees. These findings advance our understanding of the genomic changes underlying host specialization.

Resurrection of the sixgill shark Hexanchus vitulus Springer & Waller, 1969 (Hexanchiformes, Hexanchidae), with comments on its distribution in the northwest Atlantic Ocean - Toby S. Daly-Engel; Ivy E. Baremore; R. Dean Grubbs; Simon J. B. Gulak; Rachel T. Graham; Michael P. Enzenauer (Marine Biodiversity, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Facilitating Integration in Interdisciplinary Research: Lessons from a South Florida Water, Sustainability, and Climate Project - Alicia L. Lanier; Jillian R. Drabik; Tanya Heikkila; Jessica Bolson; Michael C. Sukop; David W. Watkins; Jennifer Rehage; Ali Mirchi; Victor Engel; David Letson (Environmental Management, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Temporal stability and mixed-stock analyses of humpback whales (Megaptera novaeangliae) in the nearshore waters of the Western Antarctic Peninsula - G. R. Albertson; A. S. Friedlaender; D. J. Steel; A. Aguayo-Lobo; S. L. Bonatto; S. Caballero; R. Constantine; A. L. Cypriano-Souza; M. H. Engel; C. Garrigue; L. Flórez-González; D. W. Johnston; et al. (Polar Biology, 2018)

T-protein is present in large excess over the other proteins of the glycine cleavage system in leaves of Arabidopsis - Stefan Timm; Jonas Giese; Nadja Engel; Maria Wittmiß; Alexandra Florian; Alisdair R. Fernie; Hermann Bauwe (Planta, 2018)

Brain-Defective Insulin Signaling Is Associated to Late Cognitive Impairment in Post-Septic Mice - Fernanda S. Neves; Patrícia T. Marques; Fernanda Barros‑Aragão; José Bruno Nunes; Aline M. Venancio; Danielle Cozachenco; Rudimar L. Frozza; Giselle F. Passos; Robson Costa; Jade de Oliveira; Daiane F. Engel; Andreza F. De Bem; et al. (Molecular Neurobiology, 2018)

Use of phytoproductivity data in the choice of native plant species to restore a degraded coal mining site amended with a stabilized industrial organic sludge - Claudete G. Chiochetta; Hela Toumi; Renata F. S. Böhm; Fernanda Engel; Gabriel Poyer-Radetski; Leonardo R. Rörig; Fabrizio Adani; Claudemir M. Radetski (Environmental Science and Pollution Research, 2017)

Does affective touch influence the virtual reality full body illusion? - Jutta R. de Jong; Anouk Keizer; Manja M. Engel; H. Chris Dijkerman (Experimental Brain Research, 2017)

Identification of new TRIP12 variants and detailed clinical evaluation of individuals with non-syndromic intellectual disability with or without autism - Nuria C. Bramswig; H.-J. Lüdecke; M. Pettersson; B. Albrecht; R. A. Bernier; K. Cremer; E. E. Eichler; D. Falkenstein; J. Gerdts; S. Jansen; A. Kuechler; M. Kvarnung; et al. (Human Genetics, 2017)

Influenza pathogenicity during pregnancy in women and animal models - Debby van Riel; Hans-Willi Mittrücker; Geraldine Engels; Karin Klingel; Udo R. Markert; Gülsah Gabriel (Seminars in Immunopathology, 2016)

A family-based study of gene variants and maternal folate and choline in neuroblastoma: a report from the Children’s Oncology Group - Angela L. Mazul; Anna Maria Siega-Riz; Clarice R. Weinberg; Stephanie M. Engel; Fei Zou; Kathryn S. Carrier; Patricia V. Basta; Zalman Vaksman; John M. Maris; Sharon J. Diskin; Charlene Maxen; Arlene Naranjo; et al. (Cancer Causes & Control, 2016)

The McGill Brisbane Symptom Score in relation to survival in pancreatic adenocarcinoma: a validation study - Suhail A. R. Doi; Luis Furuya-Kanamori; Jessica M. Engel; Mohammad H. Jamal; Rachel V. Stankowski; Jeffrey Barkun; Adedayo A. Onitilo (Cancer Causes & Control, 2016)

Microstructured Nickel-Titanium Thin Film Leaflets for Hybrid Tissue Engineered Heart Valves Fabricated by Magnetron Sputter Deposition - K. Loger; A. Engel; J. Haupt; R. Lima de Miranda; G. Lutter; E. Quandt (Cardiovascular Engineering and Technology, 2016)

Functional Approach to Simulating Short-Rotation Woody Crops in Process-Based Models - Tian Guo; Bernard A. Engel; Gang Shao; Jeffrey G. Arnold; Raghavan Srinivasan; James R. Kiniry (BioEnergy Research, 2015)

Generators and Connectivity of the Early Auditory Evoked Gamma Band Response - Nenad Polomac; Gregor Leicht; Guido Nolte; Christina Andreou; Till R. Schneider; Saskia Steinmann; Andreas K. Engel; Christoph Mulert (Brain Topography, 2015)

‘Splitting versus lumping’: Temple–Baraitser and Zimmermann–Laband Syndromes - Nuria C. Bramswig; C. W. Ockeloen; J. C. Czeschik; A. J. van Essen; R. Pfundt; J. Smeitink; B. T. Poll-The; H. Engels; T. M. Strom; D. Wieczorek; T. Kleefstra; H.-J. Lüdecke (Human Genetics, 2015)

Antagomirs targeting microRNA-134 increase hippocampal pyramidal neuron spine volume in vivo and protect against pilocarpine-induced status epilepticus - Eva M. Jimenez-Mateos; Tobias Engel; Paula Merino-Serrais; Isabel Fernaud-Espinosa; Natalia Rodriguez-Alvarez; James Reynolds; Cristina R. Reschke; Ronan M. Conroy; Ross C. McKiernan; Javier deFelipe; David C. Henshall (Brain Structure and Function, 2015)

Fabrication and Evaluation of Nitinol Thin Film Heart Valves - K. Loger; R. Lima de Miranda; A. Engel; M. Marczynski-Bühlow; G. Lutter; E. Quandt (Cardiovascular Engineering and Technology, 2014)

A tailored implementation strategy to reduce the duration of intravenous antibiotic treatment in community-acquired pneumonia: a controlled before-and-after study - M. F. Engel; A. H. W. Bruns; M. E. J. L. Hulscher; C. A. J. M. Gaillard; S. U. C. Sankatsing; F. Teding van Berkhout; M. H. Emmelot-Vonk; E. M. Kuck; M. H. M. Steeghs; J. H. den Breeijen; R. K. Stellato; A. I. M. Hoepelman; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Seizures during antidepressant treatment in psychiatric inpatients—results from the transnational pharmacovigilance project “Arzneimittelsicherheit in der Psychiatrie” (AMSP) 1993–2008 - M. Köster; R. Grohmann; R. R. Engel; M. A. Nitsche; E. Rüther; D. Degner (Psychopharmacology, 2013)

Long-term population size of the North Atlantic humpback whale within the context of worldwide population structure - Kristen Ruegg; Howard C. Rosenbaum; Eric C. Anderson; Marcia Engel; Anna Rothschild; C. Scott Baker; Stephen R. Palumbi (Conservation Genetics, 2013)

17 novel polymorphic microsatellite markers for the giant water bug, Abedus herberti (Belostomatidae) - T. S. Daly-Engel; R. L. Smith; D. S. Finn; M. E. Knoderbane; I. C. Phillipsen; D. A. Lytle (Conservation Genetics Resources, 2012)

Depth distribution of chironomids and an evaluation of site-specific and regional lake-depth inference models: a good model gone bad? - Les C. Cwynar; Andrew B. H. Rees; Cy R. Pedersen; Stefan Engels (Journal of Paleolimnology, 2012)

Assessing the potential for post‐copulatory sexual selection in elasmobranchs - J. L. Fitzpatrick; R. M. Kempster; T. S. Daly‐Engel; S. P. Collin; J. P. Evans (Journal of Fish Biology, 2012)
This review highlights the potential role that post‐copulatory sexual selection plays in elasmobranch reproductive systems and the utility of this group to further understanding of evolutionary responses to the post‐copulatory processes of sperm competition and cryptic female choice. The growing genetic evidence for female multiple mating (polyandry) in elasmobranchs is summarized. While polyandry appears to be common in this group, rates of multiple paternity are highly variable between species suggesting that there is large variance in the strength of post‐copulatory sexual selection among elasmobranchs. Possible adaptations of traits important for post‐copulatory sexual selection are then considered. Particular emphasis is devoted to explore the potential for sperm competition and cryptic female choice to influence the evolution of testes size, sperm morphology, genital morphology and sperm storage organs. Finally, it is argued that future work should take advantage of the wealth of information on these reproductive traits already available in elasmobranchs to gain a better understanding of how post‐copulatory sexual selection operates in this group.

Responses of native and non-native Mojave Desert winter annuals to soil disturbance and water additions - Alexis A. Suazo; Jessica E. Spencer; E. Cayenne Engel; Scott R. Abella (Biological Invasions, 2012)

Green manure and phosphate rock effects on phosphorus availability in a northern Great Plains dryland organic cropping system - Terry L. Rick; Clain A. Jones; Richard E. Engel; Perry R. Miller (Organic Agriculture, 2011)

Crustose, calcareous algal bloom (Ramicrusta sp.) overgrowing scleractinian corals, gorgonians, a hydrocoral, sponges, and other algae in Lac Bay, Bonaire, Dutch Caribbean - C. E. Eckrich; M. S. Engel; R. B. J. Peachey (Coral Reefs, 2011)

Depicting more accurate pictures of protistan community complexity using pyrosequencing of hypervariable SSU rRNA gene regions - Anke Behnke; Matthias Engel; Richard Christen; Markus Nebel; Rolf R. Klein; Thorsten Stoeck (Environmental Microbiology, 2011)
Summary Initial environmental pyrosequencing studies suggested highly complex protistan communities with phylotype richness decisively higher than previously estimated. However, recent studies on individual bacteria or artificial bacterial communities evidenced that pyrosequencing errors may skew our view of the true complexity of microbial communities. We pyrosequenced two diversity markers (hypervariable regions V4 and V9 of the small‐subunit rDNA) of an intertidal protistan model community, using the Roche GS‐FLX and the most recent GS‐FLX Titanium sequencing systems. After pyrosequencing 24 reference sequences we obtained up to 2039 unique tags (from 3879 V4 GS‐FLX Titanium reads), 77% of which were singletons. Even binning sequences that share 97% similarity still emulated a pseudodiversity exceeding the true complexity of the model community up to three times (V9 GS‐FLX). Pyrosequencing error rates were higher for V4 fragments compared with the V9 domain and for the GS‐FLX Titanium compared with the GS‐FLX system. Furthermore, this experiment revealed that error rates are taxon‐specific. As an outcome of this study we suggest a fast and efficient strategy to discriminate pyrosequencing signals from noise in order to more realistically depict the structure of protistan communities using simple tools that are implemented in standard tag data‐processing pipelines.

Recommendations to improve identification of hereditary and familial colorectal cancer in Europe - H. F. A. Vasen; G. Möslein; A. Alonso; S. Aretz; I. Bernstein; L. Bertario; I. Blanco; S. Bulow; J. Burn; G. Capella; C. Colas; C. Engel; et al. (Familial Cancer, 2010)

Feeding grounds of the western South Atlantic humpback whale population - M. H. ENGEL; A. R. MARTIN (Marine Mammal Science, 2009)

Gamma-band activity reflects multisensory matching in working memory - Daniel Senkowski; Till R. Schneider; Frithjof Tandler; Andreas K. Engel (Experimental Brain Research, 2009)

Successive soil treatment with captan or oxytetracycline affects non-target microorganisms - Z. Piotrowska-Seget; R. Engel; E. Nowak; Jacek Kozdrój (World Journal of Microbiology and Biotechnology, 2008)

Mitochondrial DNA diversity of the Southwestern Atlantic humpback whale (Megaptera novaeangliae) breeding area off Brazil, and the potential connections to Antarctic feeding areas - Márcia H. Engel; Nelson J. R. Fagundes; Howard C. Rosenbaum; Matthew S. Leslie; Paulo H. Ott; Renata Schmitt; Eduardo Secchi; Luciano Dalla Rosa; Sandro Luis Bonatto (Conservation Genetics, 2008)

The influence of coastal topography, circulation patterns, and rafting in structuring populations of an intertidal alga - J. F. MUHLIN; C. R. ENGEL; R. STESSEL; R. A. WEATHERBEE; S. H. BRAWLEY (Molecular Ecology, 2008)
Understanding the dispersal processes that influence genetic structure in marine species requires estimating gene flow in a dynamic, fluid environment that is often poorly characterized at scales relevant to multiple dispersive stages (e.g. spores, gametes, zygotes, larvae, adults). We examine genetic structure in the marine alga Fucus vesiculosus L., which inhabits moderately exposed shores in the northern Atlantic but releases gametes only under sunny, calm conditions. We predicted genetic structure would correlate with coastal topography because weather frequently varies across coastal promontories on the Maine shore when F. vesiculosus is reproductive, which causes one side to experience high levels of water motion (= no gamete release) while one side is calm (= gamete release). Furthermore, we expected that the effect of low dispersal capacities of gametes and zygotes would result in spatial genetic structure over short distances. Using surface drifters, we characterized near‐shore circulation patterns around the study sites to investigate whether directionality of gene flow was correlated with directionality of currents. We found significant genetic differentiation among sites sampled at two different peninsulas, but patterns of differentiation were unrelated to coastal topography and there was no within‐site spatial structuring. Our genetic and near‐shore circulation data, combined with an examination of gamete longevity, support the dependency of gene flow on storm‐detached, rafting, reproductive adults. This study highlights the significance of rafting as a mechanism for structuring established populations of macroalgae and associated biota and demonstrates the importance of coupling population genetics’ research with relevant hydrodynamic studies.

Entwicklung des Bergbaues in der Slowakischen Republik - J. R. Engel (BHM Berg- und Hüttenmännische Monatshefte, 2007)

Entdeckung und Erschließung der Talklagerstätte "Gemerská Poloma" Slowakei – Beschreibung der Aufschlussvarianten und der Auswahlkriterien - J. R. Engel; W. Steck (BHM Berg- und Hüttenmännische Monatshefte, 2007)

Antimicrobial activities of extracts from Indo-Pacific marine plants against marine pathogens and saprophytes - Melany P. Puglisi; Sebastian Engel; Paul R. Jensen; William Fenical (Marine Biology, 2006)

When is a hybrid a hybrid? A counter‐reply to Wallace et al . - CAROLYN R. ENGEL; CLAIRE DAGUIN; ESTER A. SERRÃO (Molecular Ecology, 2006)

Assessment of multiple paternity in single litters from three species of carcharhinid sharks in Hawaii - Toby S. Daly-Engel; R. Dean Grubbs; Kim N. Holland; Robert J. Toonen; Brian W. Bowen (Environmental Biology of Fishes, 2006)

Antimicrobial activities of extracts from tropical Atlantic marine plants against marine pathogens and saprophytes - Sebastian Engel; Melany P. Puglisi; Paul R. Jensen; William Fenical (Marine Biology, 2006)

Comparison between recombinant baculo- and adenoviral-vectors as transfer system in cardiovascular cells - G. Grassi; H. Köhn; B. Dapas; R. Farra; J. Platz; S. Engel; S. Cjsareck; R. Kandolf; C. Teutsch; R. Klima; G. Triolo; A. Kuhn (Archives of Virology, 2006)

Genetic entities and mating system in hermaphroditic Fucus spiralis and its close dioecious relative F. vesiculosus (Fucaceae, Phaeophyceae) - C. R. ENGEL; C. DAGUIN; E. A. SERRÃO (Molecular Ecology, 2005)
To date, molecular markers have not settled the question of the specific status of the closely related, but phylogenetically unresolved, brown seaweeds, hermaphroditic Fucus spiralis and dioecious Fucus vesiculosus , nor their propensity for natural hybridization. To test the degree of species integrity and to assess effect of the mating system on the population genetic structure, 288 individuals coming from parapatric (discontinuous) and sympatric (contiguous) spatial configurations at two sites were genotyped with five microsatellite loci. Using a Bayesian admixture analysis, our results show that F. spiralis and F. vesiculosus comprise clearly distinct genetic entities (clusters) generally characterized by cosexual and unisexual individuals, respectively. Genetic diversity within each entity suggests that F. spiralis reproduces primarily through selfing while F. vesiculosus is characterized by an endogamous breeding regime. Nevertheless, aberrant sexual phenotypes were observed in each cluster, no diagnostic alleles were revealed and 10% of study individuals were intermediate between the two genetic entities. This pattern can be explained by recent divergence of two taxa with retention of ancestral polymorphism or asymmetrical, introgressive hybridization. However, given (i) coincident monomorphism at three loci in spiralis clusters and (ii) that significantly more intermediates were observed in sympatric stations than in parapatric stations, we argue that interspecific gene flow has occurred after divergence of the two taxa. Finally, we show that whether recently separated or recently introgressive, the divergent breeding systems probably contribute to species integrity in these two taxa.

How to Improve Quality Assurance in Fluorometry: Fluorescence-Inherent Sources of Error and Suited Fluorescence Standards - U. Resch-Genger; K. Hoffmann; W. Nietfeld; A. Engel; J. Neukammer; R. Nitschke; B. Ebert; R. Macdonald (Journal of Fluorescence, 2005)

Miltefosine (Impavido): the first oral treatment against leishmaniasis - H. Sindermann; S. L. Croft; K. R. Engel; W. Bommer; H. J. Eibl; C. Unger; J. Engel (Medical Microbiology and Immunology, 2004)

Specific Status of Propithecus spp. - Mireya I. Mayor; Julie A. Sommer; Marlys L. Houck; John R. Zaonarivelo; Patricia C. Wright; Colleen Ingram; Stacia R. Engel; Edward E. Louis (International Journal of Primatology, 2004)

Absence of cross-modal reorganization in the primary auditory cortex of congenitally deaf cats - A. Kral; J.-H. Schrder; R. Klinke; A. K. Engel (Experimental Brain Research, 2003)

Traits of the invasive Centaurea maculosa and two native grasses: effect of N supply - P. S. Blicker; B. E. Olson; R. Engel (Plant and Soil, 2002)

Feeding habits and trophic niche overlap of two sympatric mustelidae, the polecatMustela putorius and the beech martenMartes foina - A. Baghli; E. Engel; R. Verhagen (European Journal of Wildlife Research, 2002)

Chemical Ecology of Marine Microbial Defense - Sebastian Engel; Paul R. Jensen; William Fenical (Journal of Chemical Ecology, 2002)

Multiple defensive roles for triterpene glycosides from two Caribbean sponges - Julia Kubanek; Kristen E. Whalen; Sebastian Engel; Sarah R. Kelly; Timothy P. Henkel; William Fenical; Joseph R. Pawlik (Oecologia, 2002)

Conditioned place preference for cocaine is attenuated in mice over-expressing the 5-HT 3 receptor - Allan A.; Galindo R.; Chynoweth J.; Engel S.; Savage D. (Psychopharmacology, 2001)

Validity of Prior Absorption of Serum Samples with Reiter's Spirochetes in Serological Diagnosis of Borrelia burgdorferi Infections - W. Engel; A. Vogt; S. R. Batsford (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Method for Precision Nitrogen Management in Spring Wheat: II. Implementation - Dan S. Long; Richard E. Engel; Gregg R. Carlson (Precision Agriculture, 2000)

Comparison of several approaches of therapeutic drug monitoring of cyclosporin A based on individual pharmacokinetics - R. Wacke; B. Rohde; G. Engel; G. Kundt; E. -M. Hehl; R. Bast; H. Seiter; B. Drewelow (European Journal of Clinical Pharmacology, 2000)

Method for Precision Nitrogen Management in Spring Wheat: I Fundamental Relationships - Richard E. Engel; Dan S. Long; Gregg R. Carlson; Corey Meirer (Precision Agriculture, 1999)

Combined analysis of field and model data: A case study of the phosphate dynamics in the German Bight in summer 1994 - Th. Pohlmann; Th. Raabe; R. Doerffer; S. Beddig; U. Brockmann; S. Dick; M. Engel; K. -J. Hesse; P. König; B. Mayer; A. Moll; D. Murphy; et al. (Ocean Dynamics, 1999)

5-HT 3 receptor over-expression enhances ethanol sensitivity in mice - S. R. Engel; A. M. Allan (Psychopharmacology, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Characterization of microsatellite markers in the red alga Gracilaria gracilis - H Luo; M Möorchen; C. R Engel; C Destombe; J. T Epplen; C Epplen; P Saumitou‐Laprade; M Valero (Molecular Ecology, 1999)

Increased allocation to external hyphae of arbuscular mycorrhizal fungi under CO 2 enrichment - I. R. Sanders; R. Streitwolf-Engel; M. G. A. van der Heijden; T. Boller; A. Wiemken (Oecologia, 1998)

5-HT 3 receptor over-expression decreases ethanol self administration in transgenic mice - S. R. Engel; C. R. Lyons; A. M. Allan (Psychopharmacology, 1998)

Short allele dominance as a source of heterozygote deficiency at microsatellite loci: experimental evidence at the dinucleotide locus Gv1CT in Gracilaria gracilis (Rhodophyta) - R. WATTIER; C. R. ENGEL; P. SAUMITOU‐LAPRADE; M. VALERO (Molecular Ecology, 1998)
In this study, we compared the genotypes obtained at a microsatellite locus using two methods of amplification and detection of variation in a set of individuals belonging to the red alga haplo‐diploid species, Gracilaria gracilis . The methods varied in their capacity to detect longer alleles in heterozygotes, resulting in an apparent heterozygote deficiency. We attributed this bias in favour of short alleles to competition leading to the preferential amplification of shorter alleles (short allele dominance). To test this hypothesis, we created artificial heterozygotes (mixtures of two haploid DNA samples) and showed that long alleles already less intense than short alleles, ‘suffer’ more from being in association.

The effects of an ergonomic-educational course - J. A. Engels; J. W. J. van der Gulden; T. F. Senden; J. J. Kolk; R. A. Binkhorst (International Archives of Occupational and Environmental Health, 1998)

Studies on the attractional effect of root exudates on hyphal growth of an arbuscular mycorrhizal fungus in a soil compartment-membrane system - H. Vierheilig; M. Alt-Hug; R. Engel-Streitwolf; P. Mäder; A. Wiemken (Plant and Soil, 1998)

Fluoromethylhistidine inhibits tumor growth without producing depletion of endogenous histamine - G. Cricco; N. Engel; M. Croci; C. Davio; G. Martín; C. Fitzsimons; R. Bergoc; E. Rivera (Inflammation Research, 1997)

Mast cell-mediated induction of ICAM-1, VCAM-1 and E-selectin in endothelial cells in vitro: constitutive release of inducing mediators but no effect of degranulation - Charles M. C. J. van Haaster; Josien G. Derhaag; W. Engels; Paul J. M. R. Lemmens; Annemie P. Gijsen; Gerard Hornstra; Ger J. van der Vusse; Adrian M. Duijvestijn (Pflügers Archiv - European Journal of Physiology, 1997)

Dietary modulation of fatty acid composition of mast cell phospholipids does not affect histamine release induced by compound 48/80 - W. Engels; C. M. C. J. Van Haaster; P. J. M. R. Lemmens; G. J. Van der Vusse; G. Hornstra (Inflammation Research, 1997)

European isolates of bovine herpesvirus 1: A comparison of restriction endonuclease sites, polypeptides, and reactivity with monoclonal antibodies - A. E. Metzler; H. Matile; U. Gassmann; M. Engels; R. Wyler (Archives of Virology, 1985)

Demonstration of an IgG-Fc receptor in ratcytomegalovirus infected cells - C. A. Bruggeman; R. Reinders; W. M. H. Debie; P. M. Frederik; W. Engels; C. P. A. van Boven (Archives of Virology, 1984)

Comparison of the genomes of infectious bovine rhinotracheitis and infectious pustular vulvovaginitis virus strains by restriction endonuclease analysis - Monika Engels; F. Steck; R. Wyler (Archives of Virology, 1981)